2022
DOI: 10.1002/fld.5100
|View full text |Cite
|
Sign up to set email alerts
|

A dual resolution phase‐field solver for wetting of viscoelastic droplets

Abstract: We present a new and efficient phase‐field solver for viscoelastic fluids with moving contact line based on a dual‐resolution strategy. The interface between two immiscible fluids is tracked by using the Cahn‐Hilliard phase‐field model, and the viscoelasticity incorporated into the phase‐field framework. The main challenge of this approach is to have enough resolution at the interface to approach the sharp‐interface methods. The method presented here addresses this problem by solving the phase field variable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Most models on the wetting phenomenon in literature are based on Equation ( 9), such as the work of Jacqmin, [167] Cahn, [173] de Gennes, [174] and many other references. [175][176][177][178][179] This equation is sometimes called natural boundary condition. At static equilibrium when d𝜌/dt = 0, it has been demonstrated that this boundary condition is equivalent to the Young's law.…”
Section: Thermodynamic Interpretation For the Wetting Effect On Patte...mentioning
confidence: 99%
“…Most models on the wetting phenomenon in literature are based on Equation ( 9), such as the work of Jacqmin, [167] Cahn, [173] de Gennes, [174] and many other references. [175][176][177][178][179] This equation is sometimes called natural boundary condition. At static equilibrium when d𝜌/dt = 0, it has been demonstrated that this boundary condition is equivalent to the Young's law.…”
Section: Thermodynamic Interpretation For the Wetting Effect On Patte...mentioning
confidence: 99%